Development of a Novel Hydrophilic Pin-Type Mat
Patent Information
- Application Number
- JP2024509372
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-18
- Filing Date
- 2022-08-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-08-16
Smart Images

Figure 0007936871000100 
Figure 0007936871000101 
Figure 0007936871000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a polar pinned MAT composition for use in induced self-assembly processes. [Background technology]
[0002] Self-assembly of block copolymers is a useful method for generating even smaller patterned shapes for the fabrication of microelectronic devices, achieving limiting dimensions (CD) of shapes on the order of nanoscale. Self-assembly methods are desirable to extend the resolving capabilities of microlithography techniques for repeating shapes such as arrays of contact holes or posts. Conventional lithography strategies can use ultraviolet (UV) radiation to expose a photoresist layer coated on a substrate or layered substrate through a mask. Positive or negative photoresists are useful, and these may also contain heat-resistant elements such as silicon to enable dry development using conventional integrated circuit (IC) plasma processing techniques. In positive photoresists, UV radiation passing through the mask triggers a photochemical reaction in the photoresist, causing the exposed area to be removed with a developer solution or by conventional IC plasma processing. Conversely, in negative photoresists, UV radiation passing through the mask makes the radiation-exposed area difficult to remove with a developer solution or by conventional IC plasma processing. Integrated circuit patterns, such as gates, vias, or interconnects, are then etched into the substrate or layered substrate, and the remaining photoresist is removed. When using conventional lithography exposure processes, there are limitations to the graphic dimensions of integrated circuit patterns. Further reduction of pattern dimensions is difficult to achieve using radiation exposure due to limitations related to aberrations, focus, proximity effects, the minimum achievable exposure wavelength, and the maximum achievable numerical aperture. Due to the need for large-scale integration, the circuit dimensions and graphics of devices have been continuously reduced. In the past, the final resolution of the graphic depended on the wavelength of light used to expose the photoresist, which itself has limitations. Guided (or guiding) self-assembly techniques such as graphoepitaxy and chemoepitaxy using block copolymer imaging with patterned regions on the substrate are highly desirable techniques used to improve resolution while reducing CD variation.These techniques can be used to enhance conventional UV lithography techniques or to enable higher resolution and CD control in strategies using EUV, electron beam, deep UV, or immersion lithography. Induced self-assembly (DSA) block copolymers comprise blocks of etchable copolymer units and blocks of highly etchable copolymer units, which, when coated, aligned, and etched on a substrate, provide areas of very high-density patterns.
[0003] For the guided or unguided self-assembly of a block copolymer film on a patterned or unpatterned substrate region, the self-assembly process of this block copolymer layer typically occurs during the annealing of this film covering a neutral layer. This neutral layer on a semiconductor substrate may be an unpatterned neutral layer, or, in the case of chemoepitaxy or graphoepitaxy, this neutral layer may contain graphoepitaxy or chemoepitaxy guide patterns (formed via the UV lithography technique described above). While the block copolymer film is annealed, the underlying neutral layer induces nanophase separation of the block copolymer domains. One example is the formation of layer-separated domains, which are lamellae or cylinders perpendicular to the surface of the underlying neutral layer. These nanophase-separated block copolymer domains form pre-patterns (e.g., line-and-space L / S), which can be transferred into the substrate via an etching process (e.g., plasma etching). In graphoepitaxy or chemoepitaxy, these inductive patterns can affect both pattern modification and pattern multiplication. In the case of an unpatterned neutral layer, this generates, for example, a repeating array of L / S or CH. For example, in conventional block copolymers such as poly(styrene-β-methyl methacrylate) (P(Sb-MMA)) where both blocks have similar surface energies at the BCP-air interface, this can be achieved by coating and thermal annealing the block copolymer onto a layer of non-preferential or neutral material that is grafted or crosslinked at the polymer-substrate interface.
[0004] In graphoepitaxy-induced self-assembly, block copolymers self-assemble around a substrate that has been pre-patterned using conventional lithography (ultraviolet, deep UV, electron beam, or extreme ultraviolet (EUV) exposure sources) to form repeating topographic patterns such as line / space (L / S) or contact hole (CH) patterns. In an example of an L / S-induced self-assembly array, the block copolymers can enhance pattern resolution by dividing the space in the trenches between topographic lines into finer patterns, by forming self-aligned lamellar regions that can form parallel line-space patterns of different pitches in the trenches between the pre-patterned lines. For example, microphase-separable diblock copolymers or triblock copolymers, including carbon-rich blocks resistant to plasma etching (e.g., styrene, or containing some other element such as Si, Ge, or Ti), and blocks that are highly etchable or removable by plasma, can provide high-resolution pattern definition. Examples of highly etchable blocks may include monomers that are rich in oxygen, free of heat-resistant elements, and capable of forming highly etchable blocks, such as methyl methacrylate. The plasma etching gas used in the etching process to define the self-assembling pattern is typically the same gas used in processes for manufacturing integrated circuits (ICs). In this way, much finer patterns can be generated on a typical IC substrate compared to those that can be defined by conventional lithography techniques, thus achieving pattern multiplication. Similarly, graphoepitaxy can be used to generate more intricate patterns, such as contact holes. In graphoepitaxy, appropriate block copolymers align themselves by induced self-assembly around an array of contact holes or posts defined by conventional lithography, forming a denser array of etchable and etch-resistant domains, which, when etched, results in a denser array of contact holes. As a result, graphoepitaxy has the potential to provide both pattern refinement and pattern multiplication.
[0005] In chemical epitaxy or pinned chemical epitaxy, self-assembly of block copolymers is formed on a surface having an inductive pattern, which consists of regions with different chemistry, lacking or not exhibiting significant topography (in other words, non-inductive topography) that underlies the induced self-assembly process. For example, the surface of a substrate can be patterned using conventional lithography (UV, deep UV, electron beam, EUV) to create a line-and-space (L / S) pattern of surfaces with different chemistry, where exposed areas where the surface chemistry has been alternated by radiation are alternating with unexposed areas that do not show chemical changes. These regions do not provide topographic differences but provide surface chemical differences or pinning that induce self-assembly of block copolymer segments. Specifically, the induced self-assembly of block copolymers having block segments containing etch-resistant repeating units (e.g., styrene repeating units) and fast-etchable repeating units (e.g., methyl methacrylate repeating units) allows for the precise placement of etch-resistant and fast-etchable block segments on a pattern. This technique enables the precise placement of these block copolymers and subsequent pattern transfer to a substrate after plasma or wet etching. Chemical epitaxy has the advantage of being fine-tuned by changes in chemical differences, which helps improve line edge roughness and CD control, thus enabling pattern adjustment. Other types of patterns, such as repeating contact hole (CH) arrays, can also be pattern-adjusted using chemoepitaxy.
[0006] These neutral layers are layers on the substrate or on the surface of the treated substrate that have no affinity for any of the block segments of the block copolymer used for induced self-assembly. Neutral layers are useful in the graphoepitaxy method of induced self-assembly of block copolymers because they allow for proper placement or orientation of the block polymer segments for induced self-assembly, which results in proper placement of etch-resistant and highly etchable block polymer segments on the substrate. For example, on a surface containing line-and-space patterns defined by conventional radiolithography, the neutral layer allows the block segments to be oriented so that they are perpendicular to the surface of the substrate, and such orientation is ideal for both pattern adjustment and pattern multiplication, depending on the length of the block segments in the block copolymer relative to the length between lines defined by conventional lithography. If the substrate interacts too strongly with one of the block segments, this segment will lie flat on its surface, maximizing the contact area between the segment and the substrate; such a surface will disrupt the desired vertical alignment, which can be used to achieve either pattern adjustment or pattern multiplication based on the figure produced by conventional lithography. Modifying or pinning selected small areas of the substrate to strongly interact with one block of the block copolymer, while leaving the rest of the substrate coated with a neutral layer, can be useful for aligning the domains of the block copolymer in a desired direction, and this forms the basis for pinned chemoepitaxy or graphoepitaxy used for pattern multiplication. The pinned areas may be hydrophilic, having a relatively high affinity for polar block copolymer segments, such as polymethyl methacrylate block segments in a styrene-methyl methacrylate block copolymer, or alternatively, they may be hydrophobic, having a relatively high affinity for polystyrene block segments in a styrene-methyl methacrylate block copolymer.
[0007] There is a demand for the development of a hydrophilic MAT pinning layer for DSA processing that has a simple formulation and composition that does not require the presence of small molecule surfactants that release acids thermally or photochemically. This is because such a formulation would avoid the problem of contamination that can occur in the upper block copolymer during thermal annealing, which leads to defect formation. For example, a formulation of poly(methyl methacrylate-r-2-vinyloxyethyl)P(MMA-r-VEMA) prepared with triethylammonium p-toluenesulfonate as a thermal acid generator was developed as a hydrophilic crosslinkable pinning MAT composition for use in reverse line flow DSA processing (US9,093,263 (Patent Document 1)). However, this thermal acid generator additive, which needs to be added to thermally activate the crosslinkable groups of VEMA, has been observed to cause dark spot defects when the MAT layer is thermally cured on the substrate. This causes defects in the subsequent DSA process of the poly(methyl methacrylate-b-styrene) block copolymer upper layer. In addition, the synthesis of P(MMA-r-VEMA) required post-polymerization modification using highly toxic tetramethylammonium hydroxide (TMAH) as a reagent. Such synthesis methods can be problematic when carried out on a large scale, and therefore there is a need for the development of novel hydrophilic MAT materials that are easier to scale up and do not require curing additives to catalyze crosslinking, in order to avoid the formation of defects when used as a MAT underlayer during DSA processing of the upper block copolymer. In relation to the present invention, the MAT layer is a crosslinked layer that is insoluble to any layer coated thereon and can be used as a DSA neutral or pinning layer. [Brief explanation of the drawing]
[0008] [Figure 1] A representative 1H NMR spectrum of P(MMA-r-TMOSiPrMA-r-TMSHEMA) is shown. [Figure 2]This is an SEM image showing the parallel morphology of PME-7102 (Lo=29nm, film thickness 35nm at 1500rpm) annealed at 250°C on a crosslinked film of the material used in synthesis example 2 on a silicon wafer. [Prior art documents] [Patent Documents]
[0009] [Patent Document 1] US9,093,263 [Non-patent literature]
[0010] [Non-Patent Document 1] Macromolecules 2019,52,2987-2994 [Non-Patent Document 2] Macromol.Rapid Commun.2018,39,1800479 [Non-Patent Document 3] A.Deiter Shluter et al Synthesis of Polymers,2014,Volume 1,p315 [Non-Patent Document 4] Encyclopedia of Polymer Science and Technology,2014,Vol 7,p.625 [Overview of the Initiative]
[0011] The present invention describes several different novel terpolymer hydrophilic crosslinkable MAT compositions, all of which contain a polar alkyl meth(acrylate), such as methyl methacrylate, as a main component, and whose resin component is designed to be scalable in large quantities and does not require the addition of a thermal acid generator, photoacid generator, thermal radical generator, or photoradical generator to enable curing. One of these is P(MMA-r-AMMA) [i.e., poly(methyl methacrylate-co-9-anthracene methyl methacrylate)], which does not crosslink sufficiently to hold the hydrophilic film on its own, but can be sufficiently crosslinked by adding a bismaleimide-based crosslinking agent incorporated into the crosslinked resin, and avoids the problems of contamination of the upper block copolymer and the formation of defects during DSA processing. Another approach to solving this problem was to use P(MMA-r-TMOSiPrMA) [i.e., poly(methyl methacrylate)-co-3-(trimethoxysilyl)propyl methacrylate] as the resin in the hydrophilic MAT formulation. This can be thermally crosslinked using a low-diffusion bifunctional base additive, providing excellent film retention. Another approach was to use P(MMA-r-TMOSiPrMA-r-TMSHEMA [i.e., poly(methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylate)-co-2-trimethylsilyloxyethyl methacrylate)] as the resin terpolymer. This also provides a hydrophilic, crosslinkable, pinned MAT with fewer coating defects, but without the need for the use of acidic or basic thermal or photochemical additives. In all of these polymer designs, the MMA component is required to pin the PS-b-PMMA diblock copolymer. The TMOSiPrMA component enables crosslinking and provides excellent substrate adhesion. The TMSHEMA component masks the free hydroxyl groups that would crosslink the polymer during baking. The methacrylic properties of all monomers contribute to the high hydrophilicity of this film. The fewer defects present in the cured film of these materials allow for better processing of guide patterns and, therefore, DSA of BCP, reducing the number of defects.
[0012] Another aspect of the present invention is an inventive random copolymer of Structure (A) comprising the following: · An alkyl-containing repeating unit of Structure (I), wherein R I is C1 to C8 alkyl, R m1 is H or C1 to C4 alkyl, and n1 is the total number of the repeating units; · A trialkylsilyloxy-containing repeating unit of Structure (II), wherein R II is a moiety of Structure (A-1), where R m2 is H or C1 to C4 alkyl, L1 is either a direct valence bond or a C1 to C8 alkylene moiety, R IIa , R IIb and R IIc are independently selected from C1 to C4 alkyl, and n2 is the total number of the repeating units; · At least one type of crosslinkable repeating unit of Structure (III) (wherein R III is a moiety of Structure (A-2) or (A-3)), or two different types of repeating units of Structure (III) (wherein R III is either a moiety of Structure (A-2) or a moiety of Structure (A-3)), where R S1 is C1 to C4 alkyl, R S is C1 to C4 alkyl, x is 0, 1 or 2, L2 and L3 are independently either a direct valence bond or a C1 to C10 alkylene moiety, R OX is an aliphatic moiety containing oxirane, and n3 is the total number of the repeating units; · Two terminal groups shown in Structure (A), one of which is H, and the other is a methyl moiety substituted with R r , R r1 and R r2 , where R r1 and R r2 are independently selected from C1 to C8 alkyl, and R r is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), and Ri is a C1 to C8 alkyl or aryl moiety.
[0013] [ka] Another aspect of the present invention is • It is a random copolymer: ··Structure (I) alkyl-containing repeating unit, in the formula, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl; ··At least one type of crosslinkable repeating unit derived from alkyl 2-methylene alkanoates (alkyl-OC(=O)-C(alkyl)=CH2) or alkyl methacrylates (alkyl-OC(=O)-CH=CH2), which does not require an acid catalyst for crosslinking, wherein the alkyloxy portion is substituted with a crosslinkable portion selected from the group consisting of trialkylsilyloxy, oxiranes, trialkyloxysilyls, and anthracenes; Random copolymers containing • Solvents for spin casting, Includes, • Does not contain thermal acid generators, photoacid generators, thermal radical generators, or photoradical generators. It is a composition.
[0014] [ka] Another aspect of the present invention is a process for coating these compositions and thermally generating a crosslinked polar MAT pinning layer without using a thermal acid generator, photoacid generator, thermal radical generator, or photoradical generator.
[0015] Another aspect of the present invention is the use of these crosslinked polar MAT coatings in DSA processing. [Modes for carrying out the invention]
[0016] Both the general description above and the detailed description below are illustrative and explanatory, and should be understood not to limit the invention described in the claims. In this application, unless otherwise specifically stated, the use of the singular form includes the plural, the singular form means "at least one," and the use of "or" means "and / or." Furthermore, the use of "includes," and other verb forms such as "included," is not limiting. Also, unless otherwise specifically stated, descriptions such as "element" or "component" include both elements and components containing one constituent unit, and elements or components containing more than one constituent unit. Unless otherwise indicated, the conjunction "and" used herein is intended to be compatible, and the conjunction "or" is not intended to be exclusive. For example, the phrase "or instead" is intended to be exclusive. The use of "and / or" used herein refers to any combination of the aforementioned elements, including the use of a single element.
[0017] The term C1-C4 alkyl is a general term for methyl and C2-C4 linear alkyl and C3-C4 branched alkyl moieties, and examples include methyl (-CH3), ethyl (-CH2-CH3), n-propyl (-CH2-CH2-CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2-CH2-CH2-CH3), tert-butyl (-C(CH3)3), isobutyl (CH2-CH(CH3)2), and 2-butyl (-CH(CH3)CH2-CH3). Similarly, the term C1-C8 alkyl includes methyl C2-C8 linear alkyl, C3-C8 branched alkyl, C4-C8 cycloalkyl (e.g., cyclopentyl, cyclohexyl, etc.), or C5-C8 alkylene cycloalkyl (e.g., -CH2-cyclohexyl, CH2-CH2-cyclopentyl, etc.).
[0018] The term C2-C5 alkylene encompasses both linear C2-C5 alkylene moieties (e.g., ethylene, propylene, etc.) and branched C3-C5 alkylene moieties (e.g., -CH(CH3)-, -CH(CH3)-CH2-, etc.).
[0019] Diblock and triblock copolymers of styrene-based and alkyl 2-methylene alkanoate-derived repeating unit moieties, which are useful as components in the compositions of the present invention described herein, can be produced by various methods such as anionic polymerization, atom transfer radical polymerization (ATRP), reversible addition-cleavage-chain transfer (RAFT) polymerization, and living radical polymerization (Macromolecules 2019, 52, 2987-2994 (Non-Patent Literature 1); Macromol. Rapid Commun. 2018, 39, 1800479 (Non-Patent Literature 2); A. Deiter Shluter et al Synthesis of Polymers, 2014, Volume 1, p315 (Non-Patent Literature 3); Encyclopedia of Polymer Science and Technology, 2014, Vol 7, p.625 (Non-Patent Literature 4)).
[0020] The random copolymer poly(styrene-co-methyl methacrylate) is abbreviated as "P(S-co-MMA)", and the oligomeric form of this material is also abbreviated as P(S-co-MMA). Similarly, the block copolymer poly(styrene-block-methyl methacrylate) is abbreviated as P(Sb-MMA), while the oligomeric form of this material is abbreviated as oligo(Sb-MMA). The oligomer oligo(styrene-co-p-octylstyrene)-block-(methyl methacrylate-co-di(ethylene glycol)methyl ether methacrylate) uses the same abbreviation to indicate random block copolymer elements, specifically oligo(S-co-p-OS)-bP(MMA-co-DEGMEMA) (S=styrene, p-OS=para-octylstyrene, MMA=methacrylate, DEGMEMA=di(ethylene glycol)methyl ether methacrylate) to indicate repeating units in this block copolymer where the two blocks are random copolymers.
[0021] In this application, FOV is an abbreviation for "field of view" in a top-down scanning electron microscope (SEM) image. "L / S" is an abbreviation for "line and space" lithography.
[0022] PGMEA and PGME are abbreviations for 1-methoxypropan-2-yl acetate and 1-methoxypropan-2-ol, respectively.
[0023] The chapter titles used herein are for the purpose of organizing the document and should not be interpreted as limiting the subject matter. While not limiting, all documents or parts of documents cited herein, including patents, patent applications, articles, books, and professional texts, are considered to have their entire contents included herein for all purposes. In the event of any conflict between the definition of a term in one or more of the documents and similar materials cited herein and those in this specification, the definition in this specification shall prevail.
[0024] Unless otherwise specified, “alkyl” refers to a hydrocarbon group that can be a linear, branched hydrocarbon group (e.g., methyl, ethyl, propyl, isopropyl, tert-butyl, and similar groups), a cyclic hydrocarbon group (e.g., cyclohexyl, cyclopropyl, cyclopentyl, and similar groups), or a polycyclic hydrocarbon group (e.g., norbornyl, adamantyl, and similar groups). These alkyl portions may be substituted or unsubstituted as described below. The term “alkyl” refers to such portions having C1–C8 carbon atoms. For structural reasons, linear alkyls are understood to begin at C1, branched and cyclic alkyls at C3, and polycyclic alkyls at C5. Furthermore, the portions derived from alkyls described below, e.g., alkyloxy and perfluoroalkyls, are understood to have the same carbon number range unless otherwise specified. If a different alkyl group length is specified than that described above, the above definition of alkyl remains valid in that it encompasses all types of alkyl moieties, and the above structural considerations with respect to the minimum number of carbon atoms of a given type of alkyl group still apply.
[0025] Alkyloxy (also known as alkoxy) refers to an alkyl group bonded via an oxy (-O-) moiety (e.g., methoxy, ethoxy, propoxy, butoxy, 1,2-isopropoxy, cyclopentyloxy, cyclohexyloxy, and similar compounds). These alkyloxy moieties may or may not be substituted, as described below.
[0026] A halo or halide refers to a halogen, F, Cl, Br, or I that is bonded to an organic part by a single bond.
[0027] As used herein, the term lactone encompasses both monolactones (e.g., caprolactone) and dilactones (e.g., lactides).
[0028] Haloalkyls refer to linear, cyclic, or branched saturated alkyl groups, such as those described above, in which at least one of the hydrogen atoms is replaced by a halide selected from the group consisting of F, Cl, Br, I, or a mixture of these if more than one halo moiety is present. Fluoroalkyls are a specific subgroup of these moieties.
[0029] Perfluoroalkyl groups refer to the linear, cyclic, or branched saturated alkyl groups defined above, in which all hydrogen atoms are replaced by fluorine atoms (e.g., trifluoromethyl, perfluoroethyl, perfluoroisopropyl, perfluorocyclohexyl, and similar groups).
[0030] Copolymer of structure (A) One aspect of the present invention is an inventive random copolymer of structure (A) comprising: • Alkyl-containing repeating unit in structure (I), where R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl, and n1 is the total number of repeating units; • Structure (II) contains a repeating unit containing trialkylsilyloxy, in the formula R II This is part of the structure (A-1), and here R m2 L1 is either H or C1-C4 alkyl, L1 is either a direct valence bond or a C1-C8 alkylene moiety, R IIa , R IIb and R IIc n2 is independently selected from C1-C4 alkyl groups, and n2 is the total number of repeating units; • At least one type of crosslinkable repeating unit of structure (III) (wherein R III (where R is a part of structure (A-2) or (A-3), or two different types of repeating units of structure (III) (in the formula, R III ( is either part of structure (A-2) or part of structure (A-3), where R S1 R is a C1-C4 alkyl group, Sis a C1-C4 alkyl group, x is 0, 1, or 2, and L2 and L3 are independently either a direct valence bond or a C1-C10 alkylene moiety, R OX n3 is the aliphatic moiety containing oxirane, and n3 is the total number of repeating units; The structure (A) shows two terminal groups, one of which is H and the other is R. r , R r1 and R r2 This is a methyl moiety substituted with, where R r1 and R r2 R is independently selected from C1-C8 alkyl groups, and r The cyano moiety (-CN) or carbonylalkyl moiety (-C(=O)-Ri) is a C1-C8 alkyl or aryl moiety.
[0031] [ka] In another aspect of the copolymer of structure (A) of the present invention, the repeating units essentially consist of repeating units of structures (I), (II), and (III), wherein the repeating units of structure (III) are a single type of crosslinkable repeating unit of structure (III), and R III This is a part of structure (A-2) or structure (A-3).
[0032] In another aspect of the copolymer of structure (A) of the present invention, the repeating unit essentially consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is two different types of repeating units of structure (III), where R III This is a part of structure (A-2) or structure (A-3).
[0033] In another aspect of the copolymer of the present invention of structure (A), the repeating unit consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is a single type of crosslinkable repeating unit of structure (III), and R IIIThis is a part of structure (A-2) or structure (A-3).
[0034] In another aspect of the copolymer of structure (A) of the present invention, the repeating unit consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is two different types of repeating units of structure (III), where R III This is a part of structure (A-2) or structure (A-3).
[0035] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-2). In one other aspect of this embodiment, x is 1. In one other aspect of this embodiment, x is 2. In one other aspect of this embodiment, x is 0. In yet another aspect of this embodiment, L2 is the C2-C4 alkylene portion.
[0036] In another aspect of the copolymer of the present invention of structure (A), R III R has structure (A-2a). In one aspect of this embodiment, Rs is a C1-C4 alkyl group. In another aspect of this embodiment, R III It has structure (A-2b).
[0037] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3). In one aspect of this embodiment, R III It has structure (A-3a), however, R e , R e1 and R e2 Each is individually selected from H or C1-C8 alkyl, and further, R e2 And, R e or R e1 If any of them are C1-C4 alkyl groups, then R e2 and R e is, or R e2 and R e1These may be bonded via C1-C4 alkylenes to form a cyclic ring. In one aspect of this embodiment, R e The C1-C8 alkyl portion and R e1 and R e2 is H. In one of the other aspects of this embodiment, R e and R e1 The C1-C8 alkyl portion and R e2 is H. In one of the other aspects of this embodiment, R e , R e1 and R e2 These are, individually, C1-C8 alkyl portions. In one aspect of this embodiment, R e H is H, and R e1 and R e2 R is individually a C1-C8 alkyl group. In one aspect of this embodiment, R e H is H, and R e1 The C1-C8 alkyl portion and R e2 H is H.
[0038] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III This part has structure (A-3), and this part has a more specific structure (A-3b), where cy is an integer in the range of 1 to 3.
[0039] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III It has structure (A-3), and this part has a more specific structure (A-3c).
[0040] [ka] In another aspect of the copolymer of the present invention of structure (A), RIII It has structure (A-3), R III It has structure (A-3), and this part has a more specific structure (A-3d).
[0041] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III It has structure (A-3), and this part has a more specific structure (A-3e).
[0042] [ka] In another aspect of the copolymer of the present invention of structure (A), R III L3 has structure (A-3) or is a more specific substructure of structure (A-3), i.e., one of the structures (A-3a) to (A-3e), and L3 is a direct valence bond or a C1-C2 alkylene moiety.
[0043] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III It has structure (A-3f).
[0044] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III It has the structure (A-3g).
[0045] [ka] In another aspect of the copolymer of the present invention of structure (A), R III It has structure (A-3), R III It has structure (A-3h).
[0046]
Chemical Formula
[0047]
Chemical Formula
[0048] In one of the other aspects of the copolymer of the present invention having Structure (A), in Structure (A-1), R II has Structure (A-1a).
[0049]
Chemical Formula
[0050]
Chemical Formula
[0051] In one aspect of the copolymer of the present invention having Structure (A), in the repeating unit of Structure (I), R m1 is H. In one of the other aspects, R m1 is C1 to C4 alkyl. In yet another aspect, Rm1 It is methyl.
[0052] In one embodiment of the copolymer of the present invention of structure (A), in the repeating unit of structure (II), R m2 R is a C1-C4 alkyl group. In one aspect of this embodiment, R m2 It is methyl. Another perspective is that R m2 H is H.
[0053] In one embodiment of the copolymer of the present invention of structure (A), in the repeating unit of structure (III), R m3 R is a C1-C4 alkyl group. In one aspect of this embodiment, R m3 It is methyl. Another perspective is that R m3 H is H.
[0054] In one embodiment of the copolymer of the present invention with structure (A), R m1 , R m2 and R m3 It is methyl.
[0055] In one embodiment of the copolymer of the present invention with structure (A), Rr is a cyano moiety at the terminal group. In one embodiment of the copolymer of the present invention with structure (A), Rr is a carboxyalkyl moiety at the terminal group. In one aspect of this embodiment, Ri is a C1-C8 alkyl group. In another aspect of this embodiment, Ri is an aryl group. In one embodiment of the copolymer of the present invention with structure (A), Rr1 and Rr2 are independently C1-C4 alkyl groups at the terminal group. In another aspect of this embodiment, Rr1 and Rr2 are methyl groups.
[0056] In one embodiment of the copolymer of the present invention having structure (A), the repeating unit of structure (I) has structure (Ia).
[0057] In one embodiment of the copolymer of the present invention having structure (A), the repeating unit of structure (II) has structure (IIa).
[0058] In one embodiment of the copolymer of the present invention having structure (A), the repeating unit of structure (III) has structure (IIIa).
[0059] In one embodiment of the copolymer of the present invention having structure (A), all repeating units of structure (III) have structure (IIIb).
[0060] [ka] In one embodiment of the copolymer of the present invention having structure (A), the repeating unit of structure (III) is a mixture of those having structures (IIIa) and (IIIb).
[0061] In one embodiment of the copolymer of the present invention of structure (A), the mole percentage of the repeating units of structure (I) is in the range of approximately 65 mol% to approximately 90 mol%, and the mole percentage of the repeating units of structure (II) is in the range of approximately 5 mol% to approximately 22 mol%, with respect to the total number of moles of the repeating units of structures (I), (II), and (III), and R III The repeating units of structure (III) having either part of structure (A-2) or (A-3) range in total from approximately 5 mol% to approximately 22 mol%, and the sum of the mol% of the repeating units of structures (I), (II), and (III) is equal to 100 mol%.
[0062] In one embodiment of the copolymer of the present invention having structure (A), the copolymer has structure (Aa). In one aspect of this embodiment, with respect to the total number of moles of repeating units of structures (Ia), (IIa), and (IIIa), the mole percent of repeating units of structure (Ia) ranges from about 65 mol% to about 90 mol%, the mole percent of repeating units of structure (IIa) ranges from about 5 mol% to about 22 mol%, the mole percent of repeating units of structure (IIIa) ranges from about 5 mol to about 22 mol%, and the sum of the mole percent of repeating units of structures (Ia), (IIa), and (IIIa) is equal to 100 mol%.
[0063] [ka] In one aspect of the copolymer of the present invention having structure (A), the copolymer has structure (Ab), where n1, n2, and n3 represent the number of repeating units of structures (Ia), (IIa), and (IIIb), respectively. In one aspect of this embodiment, with respect to the total number of moles of repeating units of structures (Ia), (IIa), and (IIIb), the mole percent of repeating units of structure (Ia) ranges from about 65 mol% to about 90 mol%, the mole percent of repeating units of structure (IIa) ranges from about 5 mol% to about 22 mol%, the mole percent of repeating units of structure (IIIb) ranges from about 5 mol% to about 22 mol%, and the sum of the mole percent of repeating units of structures (Ia), (IIa), and (IIIb) is equal to 100 mol%.
[0064] [ka] In one aspect of the copolymer of the present invention having structure (A), the copolymer has structure (Ac), where n1, n2, n3, and n3a represent the number of repeating units of structures (Ia), (IIa), (IIIa), and (IIIb), respectively. In one aspect of this embodiment, with respect to the total number of moles of repeating units of structures (Ia), (IIa), (IIIa), and (IIIb), the mole percent of repeating units of structure (Ia) is in the range of about 65 mol% to (preferably about 68 mol% to) about 90 mol%, the mole percent of repeating units of structure (IIa) is in the range of about 5 mol% to about 10 mol%, the total number of repeating units of structures (IIIa) and (IIIb) is in the range of about 5 mol% to about 22 mol%, and the sum of the mole percent of repeating units of structures (Ia), (IIa), (IIIa), and (IIIb) is equal to 100 mol%.
[0065] [ka] In one embodiment of the copolymer of the present invention having structure (A) described herein, the copolymer has Mw in the range of about 15,000 to about 50,000. In one other aspect of this embodiment, the copolymer also has polydispersity in the range of about 1.2 to about 2.5.
[0066] A composition comprising a random copolymer containing repeating units of structure (I) and at least one type of repeating unit containing a crosslinkable moiety selected from trialkylsilyloxy, oxiranes, trialkyloxysilyl, and anthracenes. Another aspect of the present invention is • Random copolymers including the following: ··Structure (I) alkyl-containing repeating unit, in the formula, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl; ··At least one type of crosslinkable repeating unit that does not require an acid catalyst for crosslinking, derived from alkyl 2-methylene alkanoates (alkyl-OC(=O)-C(alkyl)=CH2) or alkyl methacrylates (alkyl-OC(=O)-CH=CH2), wherein the alkyloxy moiety is substituted with a crosslinkable moiety selected from the group consisting of trialkylsilyloxy, oxiranes, trialkyloxysilyl, and anthracenes; • Solvents for spin casting, Includes, • Does not contain thermal acid generators, photoacid generators, thermal radical generators, or photoradical generators. It is a composition.
[0067] In one aspect of this embodiment, the composition comprises a random copolymer of structure (A) described below.
[0068] Another embodiment of this concept is the composition described herein, comprising random copolymers of structures (C), (D), and (E).
[0069] [ka] Composition comprising a copolymer of structure (A) and a solvent for spin casting Another aspect of the present invention is a composition comprising any one of the copolymers of structure (A) described herein and an organic solvent for spin casting.
[0070] In one aspect of this composition of the present invention, it further comprises a single crosslinking agent of structure (B), or a mixture of at least two different crosslinking agents of structure (B), where L5 is a C4-C8 alkylene, which has a length of at least four carbon atoms, and R a1 , R a2 , R a3 and R a4 L5 is independently selected from C4-C8 alkyl groups. In one aspect of this embodiment, L5 is a C4-C6 alkylene. In one other aspect, it has structure (B-1). In one aspect of these embodiments, R a1 , R a2 , R a3 and R a4 R is a C3-C6 alkyl group. In yet another aspect of these embodiments, R a1 , R a2 , R a3 and R a4 It is n-butyl. From another perspective, this crosslinking agent has structure (B-2).
[0071] [ka] In one aspect of this composition of the present invention, it comprises a single type of crosslinking agent of structure (B), (B-1), or (B-2).
[0072] In one aspect of this composition of the present invention, it comprises a mixture of at least two different types of crosslinking agents having structures (B), (B-1), or (B-2).
[0073] In one aspect of this composition, it comprises the copolymer in an amount of about 0.2% to about 2.0% by weight, and the spin-casting organic solvent in an amount of about 98.0% to about 99.8% by weight, the sum of these weight percentage ranges being 100% by weight or less. In one aspect of this embodiment, it consists of only these two components.
[0074] In one aspect of this composition, it comprises the copolymer in an amount of about 0.2% to about 2.0% by weight, the crosslinking agent in an amount of about 0.02% to about 0.04% by weight, and the spin-casting solvent in an amount of about 98.0% to about 99.8% by weight, where the sum of these weight percentage ranges is equal to 100% by weight. In one aspect of this embodiment, it comprises only these three components.
[0075] In one embodiment of a composition comprising the copolymer of structure (A) described herein, these do not contain a thermal acid generator, a photoacid generator, a thermal radical generator, or a photoradical generator.
[0076] A composition comprising a copolymer of structure (C), a crosslinking agent of structure (M-1), and an organic solvent for spin casting. Another aspect of the present invention is • Random copolymers having structure (C), including the following: ··Structure (I) alkyl-containing repeating unit, in the formula, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl, and n1 is the total number of repeating units; ··Structure (IV) Anthracene-containing repeating unit, in the formula, R m4 is H or C1-C4 alkyl, L4 is C1-C8 alkylene, and n4 is the total number of repeating units; The structure (C) shows two terminal groups, one of which is H, and the other is a methyl moiety substituted with Rr, Rr1, and Rr2, where Rr1 and Rr2 are independently selected from C1-C8 alkyl groups, and Rr is a cyano moiety (-CN) or carbonyl alkyl moiety (-C(=O)-Ri), and Ri is a C1-C8 alkyl or aryl moiety; • At least one crosslinking agent of structure (M-1), or a mixture of at least two different crosslinking agents of structure (M-1), however, ··L is a linking group selected from C1-C8 linear alkylene, C2-C8 branched alkylene, C6-C20 alkylene-oxy-alkylene linking group, C6-C20 alkylene-oxy-alkylene-oxy-alkylene linking group, aryl linking group having structure (M-1a), and bis-aryl linking group having structure (M-1b), and in structures (M-1a) and (M-1b),
[0077] [ka] These indicate the bonding points of these linking groups. ··R bm , R bm1 , and R bm2 These are independently selected from H and C1-C8 alkyl groups. ··X is either a direct valence bond or a linking group selected from the group consisting of sulfone (-S(=O)2-), sulfoxide (-S(=O)-), carbonyl (-C(=O)-), carbonate (-OC(=O)-O), oxycarbonyl (-OC(=O)-), carbonyloxy (-C(=O)-O-), C1-C8 linear alkylene spacer, C2-C8 branched alkylene, C5-C8 cyclic alkylene, oxy (-O-), and sulfide (-S-); • Organic solvents for spin casting; It is a composition containing [the specified ingredient].
[0078] [ka] In one aspect of this composition, the copolymer of structure (C) consists essentially of repeating units of structures (I) and (IV).
[0079] In another aspect of this composition, the copolymer of structure (C) has a molar percentage of repeating units of structure (I) ranging from about 70 mol% to about 90 mol%, and a molar percentage of repeating units of structure (IV) ranging from about 10 mol% to about 30 mol%, and furthermore, the sum of the molar percentages of repeating units of structures (I) and (IV) is equal to 100 mol%. In another aspect of this embodiment, the copolymer has a Mw ranging from about 15,000 to about 120,000. In another aspect of this embodiment, the copolymer has a polydispersity ranging from 1.2 to about 2.5.
[0080] In another embodiment of this composition, the copolymer of structure (C) has R in the repeating unit of structure (I). I The C1-C4 alkyl group is one such C1-C4 alkyl group. In another aspect of this embodiment, R I It is a C1-C3 alkyl group. From another perspective, R I is methyl or ethyl. Furthermore, from another perspective, R I is methyl. In one other aspect of this composition, the copolymer of structure (C) is such that L4 is a C1-C4 alkylene in the repeating unit of structure (IV). In another aspect of this aspect, L4 is a C1-C2 alkylene. In yet another aspect of this aspect, the repeating unit of structure (IV) has structure (IVa). In another aspect of these aspects, R m1 and R m2 R is individually selected from C1-C4 alkyl groups. In one aspect of this embodiment, R m1 and R m2 is methyl. In yet another aspect of this embodiment, R m1 and R m2 H is H.
[0081] [ka] In another aspect of this composition, the copolymer of structure (C) has a molar percentage of repeating units of structure (I) ranging from about 70 mol% to about 90 mol%, and a molar percentage of repeating units of structure (IV) ranging from about 10 mol% to about 30 mol%, and furthermore, the sum of the molar percentages of repeating units of structures (I) and (IV) is equal to 100 mol%. In another aspect of this embodiment, the copolymer has a Mw ranging from about 15,000 to about 120,000. In another aspect of this embodiment, the copolymer has a polydispersity ranging from 1.2 to about 2.5.
[0082] In one other aspect of this composition, the copolymer of structure (C) has structure (C-1). In another aspect of this aspect, the mol% of repeating units of structure (Ia) is in the range of about 70 mol% to about 90 mol%, and the mol% of repeating units of structure (IVa) is in the range of about 10 mol% to about 30 mol%, where the sum of the mol% of repeating units of structures (Ia) and (IVa) is equal to 100 mol%. In another aspect of this aspect, the copolymer has Mw in the range of about 15,000 to about 120,000. In another aspect of this aspect, the copolymer has polydispersity in the range of 1.2 to about 2.5.
[0083] [ka] In another embodiment of this composition, the crosslinking agent of structure (M-1) has structures (M-1c), (M-1d), (M-1e), (M-1f), (M-1g), (M-1h), or is a mixture of at least two thereof.
[0084] [ka] In one other aspect of the composition, it consists of from about 0.2 wt% to about 2.0 wt% of the copolymer, from about 0.02 wt% to about 0.04 wt% of the crosslinking agent, and from about 98.0 wt% to about 99.8 wt% of the organic solvent for spin casting, wherein the sum of these weight percentage ranges equals 100 wt%.
[0085] In one other aspect of this composition, the crosslinking agent is one type of crosslinking agent of structure (M-1).
[0086] In one other aspect of this composition, the crosslinking agent is at least two different types of crosslinking agents of structure (M-1).
[0087] In one aspect of the composition comprising the copolymer of structure (C) described herein, they do not comprise a thermal acid generator, a photoacid generator, a thermal radical generator or a photoradical generator.
[0088] A composition comprising a copolymer of structure (D), a crosslinking agent of structure (B), and an organic solvent for spin casting One other aspect of the present invention relates to · A random copolymer having structure (D), comprising the following; ·· An alkyl-containing repeating unit of structure (I), wherein R I is C1 to C8 alkyl, and R m1 is H or C1 to C4 alkyl, and n1 is the total number of the repeating units; ·· A crosslinkable repeating unit of structure (III), wherein R m3 is H or C1 to C4 alkyl, and R v is a moiety of structure (A-2), wherein R III is a moiety of structure (A-2), wherein Rs1 is C1 to C4 alkyl, Rs is C1 to C4 alkyl, x is 0, 1 or 2, L2 is either a direct valence bond or a C1 to C10 alkylene moiety, and n3 is the total number of the repeating units; ··two terminal groups shown in Structure (D), one of which is H, and the other is a methyl moiety substituted with Rr, Rr1 and Rr2, wherein Rr1 and Rr2 are each independently selected from C1 to C8 alkyl, Rr is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), and Ri herein is a C1 to C8 alkyl or aryl moiety; ·at least one crosslinking agent of Structure (B), wherein L5 is C4 to C8 alkylene having a length of at least 4 carbon atoms, and R a1 , R a2 , R a3 and R a4 are each independently selected from C4 to C8 alkyl; and ·an organic solvent for spin casting; is a composition containing the same.
[0089]
Chemical Formula
[0090] In one other aspect of this composition, for the aforementioned copolymer of Structure (D), with respect to the repeating unit of Structure (I), R I is C1 to C4 alkyl. In one other viewpoint of this aspect, R I is C1 to C3 alkyl. In one other viewpoint of this aspect, R I is methyl or ethyl. In yet still another viewpoint of this aspect, R I is methyl.
[0091] In one other aspect of this composition, the aforementioned copolymer of Structure (D) is such that Rm1 is C1 to C4 alkyl. In one other viewpoint of this aspect, Rm1 is methyl.
[0092] In another embodiment of this composition, the copolymer of structure (D) is such that Rm1 is H.
[0093] In one other aspect of this composition, the copolymer of structure (D) is such that x is 1 in structure (A-2). In another aspect of this aspect, it is such that x is 2 in structure (A-2). In another aspect of this aspect, it is such that x is 0 in structure (A-2).
[0094] In another embodiment of this composition, the copolymer of structure (D) is such that L2 in structure (A-2) is a C2-C4 alkylene moiety.
[0095] In one other embodiment of this composition, the copolymer of structure (D) is R III This has structure (A-2a).
[0096] In another embodiment of this composition, the copolymer of structure (D) is such that Rs is C1-C4 alkyl.
[0097] In one other embodiment of this composition, the copolymer of structure (D) is R III This has the structure (A-2b).
[0098] [ka] In one other embodiment of this composition, the copolymer of structure (D) is R m3 The C1-C4 alkyl group is one such C1-C4 alkyl group. In another aspect of this embodiment, R m3 It is methyl.
[0099] In one other embodiment of this composition, the copolymer of structure (D) is R m3 This is the case where H is the value.
[0100] In another aspect of this composition, the copolymer of structure (D) is such that in the polymer of structure (D), the mole% of the repeating unit of structure (I) ranges from about 70 mol% to about 90 mol%, and the mole% of the repeating unit of structure (III) ranges from about 5 mol% (preferably from about 10 mol%) to about 30 mol%, wherein the sum of the mole% of the repeating units of structures (I) and (III) is equal to 100 mol%.
[0101] In another aspect of this composition, the copolymer of structure (D) has structure (Db).
[0102]
Chemical Formula
[0103] In another aspect of this composition, the copolymer of structure (Db) is such that the mole% of the repeating unit of structure (Ia) ranges from about 70 mol% to about 90 mol%, and the mole% of the repeating unit of structure (IIIb) ranges from about 10 mol% to about 30 mol%, wherein the sum of the mole% of the repeating units of structures (Ia) and (IIIb) is equal to 100 mol%.
[0104] In another aspect of this composition, in the crosslinking agent of structure (B), L5 is C4 to C6 alkylene. In another aspect of this embodiment, the crosslinking agent of structure (B) has structure (B-1).
[0105] In another aspect of this composition, in the crosslinking agent of structure (B) or (B-1), R a1 , R a2 , R a3 and R a4 are C3 to C6 alkyl. In another aspect of this embodiment, R a1, R a2 , R a3 and R a4 is n-butyl. In yet another aspect of this embodiment, the crosslinking agent has structure (B-1). In yet another aspect of this embodiment, the crosslinking agent has structure (B-2).
[0106] [ka] In another embodiment of this composition, it comprises the copolymer having structure (D) or (Db) in an amount from about 0.2% by weight to about 2.0% by weight, the crosslinking agent having structure (B), (B-1), or (B-2) in an amount from about 0.02% by weight to about 0.04% by weight, and the spin-casting solvent in an amount from about 98.0% by weight to about 99.8% by weight, where the sum of these weight percentage ranges is equal to 100% by weight.
[0107] In one other embodiment of this composition, the crosslinking agent is a crosslinking agent of one type of structure (B-1). In another other embodiment of this composition, the crosslinking agent is at least two different crosslinking agents of structure (B-1).
[0108] In one embodiment of a composition comprising the copolymer of structure (D) described herein, these do not contain a thermal acid generator, a photoacid generator, a thermal radical generator, or a photoradical generator.
[0109] Composition comprising a random copolymer of structure (E) and an organic solvent for spin casting. Another aspect of the present invention is • Random copolymers of structure (E), including the following: ··Structure (I) alkyl-containing repeating unit, in the formula, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl, and n1 is the total number of repeating units; ··Repeating unit of structure (IIIc), however, R m3c is H or C1-C4 alkyl, R IIIAcis part of structure (A-2), where L2 is either a direct valence bond or a C1-C10 alkylene moiety, Rs1 is a C1-C4 alkyl, Rs is a C1-C4 alkyl, x is 0, 1, or 2, and n3c is the total number of repeating units; ··The repeating unit of structure (IIId), in the formula, R m3d is H or C1-C4 alkyl, R IIIAd This is part of structure (A-3), where L3 is either a direct valence bond or a C1-C10 alkylene moiety, and R ox is an aliphatic moiety containing oxirane, and n3d is the total number of repeating units; and ··The structure (A) shows two terminal groups, one of which is H, and the other is a methyl moiety substituted with Rr, Rr1 and Rr2, where Rr1 and Rr2 are independently selected from C1-C8 alkyl groups, and Rr is a cyano moiety (-CN) or a carbonyl alkyl moiety (-C(=O)-Ri), where Ri is a C1-C8 alkyl or aryl moiety; and • Organic solvents for spin casting; It is a composition containing [the specified ingredient].
[0110] [ka] In one other aspect of this composition, in the copolymer of structure (E), x is 1. In another aspect of this embodiment, x is 2. In yet another aspect of this embodiment, x is 0.
[0111] In another embodiment of this composition, in the copolymer of structure (E), L2 is a C2-C4 alkylene moiety.
[0112] In another embodiment of this composition, in the copolymer of structure (E), R IIIAC It has structure (A-2a).
[0113] [ka] In another embodiment of this composition, in the copolymer of structure (E), Rs is a C1-C4 alkyl group.
[0114] In another embodiment of this composition, in the copolymer of structure (E), R IIIAc It has structure (A-2b).
[0115] [ka] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3a), where R e , R e1 and R e2 These are individually selected from H or C1-C8 alkyl, and further, R e2 And, R e or R e1 If either of them is a C1-C4 alkyl group, R e2 and R e , or R e2 and R e1 These may be bonded via C1-C4 alkylenes to form a cyclic ring.
[0116] In another embodiment of this composition, in the copolymer of structure (E), R e The C1-C8 alkyl portion is R e1 and R e2 is H. In one of the other aspects of this embodiment, R e and R e1 The C1-C8 alkyl portion is R e2 is H. In one of the other aspects of this embodiment, R e , R e1 and R e2 These are individually C1-C8 alkyl portions. In yet another aspect of this embodiment, R e H is H, and R e1 and R e2 These are individually C1-C8 alkyl portions. In yet another aspect of this embodiment, R e H is Re1 The C1-C8 alkyl portion and R e2 H is H.
[0117] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd The structure (A-3b) is such that cy is an integer in the range of 1 to 3.
[0118] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3c).
[0119] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3d).
[0120] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3e).
[0121] In another embodiment of this composition, in the copolymer of structure (E), L3 is a direct valence bond or a C1-C2 alkylene moiety.
[0122] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3f).
[0123] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has the structure (A-3g).
[0124] In another embodiment of this composition, in the copolymer of structure (E), R IIIAd It has structure (A-3h).
[0125] [ka] In another embodiment of this composition, in the copolymer of structure (E), R I R is a C1-C4 alkyl group. In one aspect of this embodiment, R I is a C1-C3 alkyl group. In yet another aspect of this embodiment, R I is methyl or ethyl. In yet another aspect of this embodiment, R I It is methyl.
[0126] In another embodiment of this composition, in the copolymer of structure (E), R I is H. In another embodiment of this composition, in the copolymer of structure (E), R m1 H is H.
[0127] In another embodiment of this composition, in the copolymer of structure (E), R m3c R is a C1-C4 alkyl group. In one aspect of this embodiment, R m3c It is methyl.
[0128] In another embodiment of this composition, in the copolymer of structure (E), R m3c H is H.
[0129] In another embodiment of this composition, in the copolymer of structure (E), R m3d R is a C1-C4 alkyl group. In one aspect of this embodiment, R m3d It is methyl.
[0130] In another embodiment of this composition, in the copolymer of structure (E), R m3d H is H.
[0131] In another embodiment of this composition, in the copolymer of structure (E), R m1 , R m3c and R m3d It is methyl.
[0132] In another embodiment of this composition, in the copolymer of structure (E), Rr is a cyano moiety.
[0133] In another aspect of this composition, in the copolymer of structure (E), Rr is a carboxyalkyl moiety. In another aspect of this aspect, Ri is a C1-C8 alkyl group. In another aspect of this aspect, Ri is an aryl group.
[0134] In another aspect of this composition, in the copolymer of structure (E), Rr1 and Rr2 are independently C1-C4 alkyl groups. In another aspect of this embodiment, Rr1 and Rr2 are methyl groups.
[0135] In another embodiment of this composition, in the copolymer of structure (E), the repeating unit of structure (I) has structure (Ia).
[0136] In another embodiment of this composition, in the copolymer of structure (E), the repeating unit of structure (IIId) has structure (IIIa).
[0137] In another embodiment of this composition, in the copolymer of structure (E), the repeating unit of structure (IIIc) has structure (IIIb).
[0138] [ka] In another embodiment of this composition, in the copolymer of structure (E), the mol% of the repeating units of structure (I) is in the range of about 70 mol% to about 90 mol%, the mol% of the repeating units of structure (IIIc) is in the range of about 5 mol% to about 22 mol%, and the mol% of the repeating units of structure (IIId) is in the range of about 5 mol% to about 22 mol%, furthermore, the sum of the mol%s of the repeating units of structures (I), (IIIc), and (IIId) is equal to 100 mol%.
[0139] In another embodiment of this composition, the copolymer of structure (E) has structure (E-1). In one aspect of this embodiment, the mol% of the repeating units of structure (Ia) ranges from about 70 mol% to about 90 mol%, the mol% of the repeating units of structure (IIIb) ranges from about 5 mol% to about 22 mol%, and the mol% of the repeating units of structure (IIIa) ranges from about 5 mol% to about 22 mol%, further, the sum of the mol% of the repeating units of structures (Ia), (IIIb), and (IIIa) is equal to 100 mol%.
[0140] [ka] In one other aspect of this composition, the copolymer of structure (E) or the copolymer of structure (E-1) has a Mw in the range of about 15,000 to about 120,000. In another aspect of this embodiment, the copolymer has polydispersity in the range of 1.2 to about 6.
[0141] In one other embodiment of this composition, it further comprises a single crosslinking agent of structure (B) or a mixture of at least two different crosslinking agents of structure (B), where L5 is a C4-C8 alkylene having a length of at least four carbon atoms, and R a1 , R a2 , R a3 and R a4 L5 is independently selected from C4-C8 alkyl groups. In one aspect of this embodiment, L5 is a C4-C6 alkylene. In another aspect of this embodiment, the crosslinking agent has structure (B-1). In another aspect of the crosslinking agent, R a1 , R a2 , R a3 and R a4 R is a C3-C6 alkyl group. In yet another aspect of this embodiment, a1 , R a2 , R a3 and R a4 It is n-butyl.
[0142] In one other embodiment of this composition comprising a single crosslinking agent, the crosslinking agent has structure (B-1). In one aspect of this embodiment, R a1 , R a2 , R a3 and R a4 R is a C3-C6 alkyl group. In one aspect of this embodiment, R a1 , R a2 , R a3 and R a4 It is n-butyl.
[0143] In another embodiment of this composition, it comprises the copolymer in an amount of about 0.2% by weight to about 2.0% by weight, and the spin-casting organic solvent in an amount of about 98.0% by weight to about 99.8% by weight, where the sum of these weight percentage ranges is 100% by weight or less.
[0144] In another embodiment of this composition, it comprises the copolymer in an amount of about 0.2% to about 0.5% by weight, the crosslinking agent in an amount of about 0.02% to about 0.04% by weight, and the spin-casting organic solvent in an amount of about 99.5% to about 99.8% by weight, where the sum of these weight percentage ranges is equal to 100% by weight.
[0145] In one other embodiment of this composition comprising a single crosslinking agent, the crosslinking agent has structure (B-2).
[0146] [ka] Organic solvents for spincasting for compositions described herein Suitable solvents for use in the compositions of the present invention described herein, comprising copolymers of structure (A), (C), (D), or (E) and any of the above-described substructures thereof, are any organic solvents used for spin-casting materials such as photoresists, bottom anti-reflective coatings, or other types of organic coatings using lithography of semiconductor materials. In one other aspect of the compositions of the present invention described herein, the organic spin-casting solvent is a solvent capable of dissolving the random copolymer and other additional optional components such as those described herein. This organic spin-casting solvent may be a single solvent or a mixture of several solvents.Suitable solvents are organic solvents, including, for example, glycol ether derivatives such as ethyl cellosolve, methyl cellosolve, propylene glycol monomethyl ether (PGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol dimethyl ether, propylene glycol n-propyl ether, or diethylene glycol dimethyl ether; glycol ether ester derivatives such as ethyl cellosolve acetate, methyl cellosolve acetate, or propylene glycol monomethyl ether acetate (PGMEA); carboxylates such as ethyl acetate, n-butyl acetate, and amyl acetate; carboxylates of dibasic acids such as diethyl oxylate and dimethyl malonate; dicarboxylates of glycols such as ethylene glycol diacetate and propylene glycol diacetate; and hydroxyglycerides. Examples include methyl lactate, ethyl lactate (EL), ethyl glycolate, and ethyl 3-hydroxypropionate; ketone esters, such as methyl pyruvate or ethyl pyruvate; alkyloxycarboxylic acid esters, such as methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 2-hydroxy-2-methylpropionate, or methyl ethoxypropionate; ketone derivatives, such as methyl ethyl ketone, acetylacetone, cyclopentanone, cyclohexanone, or 2-heptanone; ketone ether derivatives, such as methyl diacetone alcohol ether; ketone alcohol derivatives, such as acetol or diacetone alcohol; ketals or acetals, such as 1,3-dioxalane and diethoxypropane; lactones, such as butyrolactone; amide derivatives, such as dimethylacetamide or dimethylformamide, anisole, and mixtures thereof.
[0147] A method using a composition containing a copolymer of structure (A). Another aspect of the present invention is a method for forming a crosslinked pinning film using any one of the compositions described herein, comprising the copolymer of structure (A), the following steps: i) A step of coating a substrate with any one of the compositions comprising the copolymer of structure (A) described herein; ii) A step of crosslinking the coated substrate by baking it in air at a temperature of approximately 230 to 250°C for approximately 30 seconds to 3 minutes; iii) Wash with a cleaning solution for approximately 1 to 4 minutes to remove soluble material; iv) Dry the coating to form the crosslinked pinning layer on the substrate; The method includes the above.
[0148] Another aspect of the present invention is a method for inducing a multiplication pattern in a block copolymer film using the copolymer of structure (A) described herein, the following steps: ia) A step of providing a block copolymer having two or more spontaneously separating blocks; iia) Step of providing the substrate; iiia) A step of forming a crosslinked pinning layer according to the above process steps i) to iv); and iva) The step of placing the block copolymer on at least a portion of the crosslinked pinning layer; The method includes the above.
[0149] Another perspective on this method is that it may further include the following steps: va) The step of forming a pattern in the crosslinked pinning layer by a lithography process before placing the block copolymer; and (via) optionally, a second coating is provided in the pattern, wherein the second coating is a neutral layer.
[0150] A method using a composition containing a copolymer of structure (C).
[0151] Another aspect of the present invention is a method for forming a crosslinked pinning film using any one of the compositions described herein, comprising the copolymer of structure (C), the following steps: ib) A step of coating a substrate with any one of the compositions comprising the copolymer of structure (C) described herein; iib) A step of crosslinking the coated substrate by baking it in air at a temperature of approximately 230 to approximately 250°C for approximately 30 seconds to approximately 30 minutes; iiib) Wash with a washing solution for approximately 1 to 4 minutes to remove soluble material; ivb) A step of drying the coating to form the crosslinked pinning layer on the substrate; The method includes the above.
[0152] Another aspect of the present invention is a method for inducing a multiplication pattern in a block copolymer film using the copolymer of structure (C) described herein, the following steps: ic) A step of providing a block copolymer having two or more spontaneously separating blocks; iic) Step of providing the substrate; ii) step of forming a crosslinked pinning layer according to the description in steps ib) to ivb); and IVC) The step of placing the block copolymer on at least a portion of the crosslinked pinning layer; The method includes the above.
[0153] Another perspective on this method is that it may further include the following steps: vc) A step of forming a pattern in the crosslinked pinning layer by a lithography process before placing the block copolymer; and vic) optionally, provide a second coating in the pattern, wherein the second coating is a neutral layer.
[0154] A method using a composition containing a copolymer of structure (D).
[0155] Another aspect of the present invention is a method for forming a crosslinked pinning film using any one of the compositions described herein, comprising the copolymer of structure (D), the following steps: id) A step of coating a substrate with one of the compositions comprising the copolymer of structure (D) described herein; iid) A step of crosslinking the coated substrate by baking it in air at a temperature of approximately 230 to 250°C for approximately 30 seconds to 3 minutes; iiid) Wash with a cleaning solution for approximately 1 to 4 minutes to remove soluble material; ivd) drying the coating to form the crosslinked pinning layer on the substrate; This method includes [something].
[0156] Another aspect of the present invention is a method for inducing a multiplication pattern in a block copolymer film using the copolymer of structure (D) described herein, the following steps: i) a step of providing a block copolymer having two or more spontaneously separating blocks; iie) Step of providing the substrate; iiie) the step of forming a crosslinked pinning layer as described in steps id) to ivd); and ive) A step of placing a block copolymer on at least a portion of the crosslinked pinning layer; The method includes the above.
[0157] Another perspective on this method is that it may further include the following steps: ve) The step of forming a pattern in the crosslinked pinning layer by a lithography process before placing the block copolymer; and vie) optionally, a second coating is provided in the pattern, wherein the second coating is a neutral layer.
[0158] A method using a composition containing a copolymer of structure (E).
[0159] Another aspect of the present invention is a method for forming a crosslinked pinning film using any one of the compositions described herein, comprising the copolymer of structure (E), the following steps: if) a step of coating a substrate with any one of the compositions comprising the copolymer of structure (E) described herein; iif) A step of crosslinking the coated substrate by baking it in air at a temperature of approximately 230°C to approximately 250°C for approximately 30 seconds to approximately 30 minutes; iiif) Wash with a cleaning solution for approximately 1 to 4 minutes to remove soluble material; ivf) drying the coating to form the crosslinked pinning layer on the substrate; The method includes the above.
[0160] Another aspect of the present invention is a method for inducing a multiplication pattern in a block copolymer film using the copolymer of structure (E) described herein, the following steps: ig) A step of providing a block copolymer having two or more spontaneously separating blocks; iig) Step of providing the substrate; iiig) the step of forming a crosslinked pinning layer as described in steps if) to ivf); and ivg) The step of placing a block copolymer on at least a portion of the crosslinked pinning layer; The method includes the above.
[0161] Another perspective on this method is that it may further include the following steps: vg) A step of forming a pattern in the crosslinked pinning layer by a lithography process before arranging the block copolymer; and vig) optionally, provide a second coating in the pattern, wherein the second coating is a neutral layer.
[0162] Another aspect of the present invention is the use of the above copolymer or composition for forming a crosslinked pinning film on a substrate or for inducing a multiplication pattern in a block copolymer film. [Examples]
[0163] chemicals Unless otherwise indicated, all chemicals were purchased from Sigma-Aldrich GmbH (3050 Spruce Street, St. Louis, MO63103).
[0164] All synthesis experiments were performed in an N2 atmosphere. Lithography experiments were performed as described herein. The molecular weight of the copolymer was measured using gel permeation chromatography at 100 Å, 500 Å, and 10 3 Å, 10 5 Å and 10 6 Gel permeation chromatography with Åμ-Ultrastylagel column Lithography experiments were performed using the TEL Clean ACT8 track. SEM images were taken using the Applied Materials NanoSEM_3D. Manipulation electron microscope images are shown at 1FOV or 2FOV magnification (field of view (FOV) = 5 μm).
[0165] Etching experiments were performed using standard isotropic oxygen etching conditions for self-assembling film block copolymers of methyl methacrylate and styrene.
[0166] Unless otherwise instructed, molecular weight measurement (also known as M n (Polydispersible) was measured using THF solvent as the eluent at 100 Å, 500 Å, and 10 3 Å, 10 5 Å and 10 6 The analysis was performed using gel permeation chromatography (PSS Inc., Germany) equipped with an Åμ-Ultristor gel column. Polystyrene polymer standards were used for calibration.
[0167] 1The 1H NMR spectrum was recorded using a Bruker Advanced III 400MHz spectrometer.
[0168] The molecular weight of the copolymer was determined using gel permeation chromatography. Unless otherwise stated, the chemicals were obtained from Sigma-Aldrich Corporation (St. Louis, Missouri).
[0169] Lithography experiments were performed using the TEL Clean ACT8 track. SEM images were taken using the Applied Materials NanoSEM_3D. Scanning electron microscope images are shown at 1FOV or 2FOV magnification (5 μm using field of view (FOV) = 1, 2, and 5FOV).
[0170] Etching experiments were performed using standard isotropic oxygen etching conditions for self-assembling film block copolymers of methyl methacrylate and styrene.
[0171] Unless otherwise instructed, molecular weight measurement (also known as M n (Polydispersible) was measured using THF solvent as the eluent at 100 Å, 500 Å, and 10 3 Å, 10 5 Å and 10 6 The analysis was performed using gel permeation chromatography (PSS Inc., Germany) equipped with an Åμ-Ultristor gel column. Polystyrene polymer standards were used for calibration.
[0172] Synthesis of polymer materials for testing Reference polymer synthesis example: Synthesis of P(Sb-MMA)(26k-b-30k) P(Sb-MMA)(26K-b-30K) was synthesized using the same procedure as described in Example 2. The amounts of initiator and monomer were varied to achieve the desired Mn and PS-PMMA block compositions. Briefly, 20 g (0.192 mol) of styrene was polymerized with 0.55 mL (1.4 M solution) of sec-butyllithium. Then, 0.164 g (0.0007 mol) of 1,1'-diphenylethylene (DPE) in 2.5 mL of anhydrous toluene was added to the reactor via an ampoule. The orange color of the reaction mixture changed to a dark reddish-brick color. This suggests that the styryllithium active center was converted to a delocalized DPE-added carbanion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken for PS block molecular weight analysis. Then, methyl methacrylate (22.85 g, 0.23 mol) was added via an ampoule. This reaction was stopped after 30 minutes using 1 mL of degassed methanol. The block copolymer was recovered by precipitation in excess isopropanol (5 times the amount of polymer solution) containing 10% water, filtered, and dried under vacuum at 55°C for 12 hours to obtain 40 g of P(Sb-MMA) consisting of 46.9 mol% polystyrene block and 53.1 mol% polymethyl methacrylate block (yield 94%).
[0173] 100 Å, 500 Å, 10 3 Å, 10 5 Å and 10 6 Gel permeabilization chromatography with an Åμ-Ultrilla gel column showed that the first P(SPDE) block was 45,048 g / mol M in PS calibration standard equivalent. n (GPC) and 1.04 M w / M n It was shown that it possessed the following properties. The molecular weight of the diblock copolymer obtained from GPC is M n,PS-b-PMMA = 46,978 g / mol and M w / M n = 1.02.
[0174] All chemicals are available from Millipore-Sigma unless otherwise stated. 9-Anthracenemethyl methacrylate is available from Shanghai B&C. NMR was measured using a Bruker 400 MHz Avance III spectrometer. GPC was measured using an Agilent system.
[0175] Polymer Synthesis Example 1: Synthesis of the polymer poly(methyl methacrylate-co-9-anthracene methyl methacrylate (80 / 20): Methyl methacrylate (40.05 g, 0.40 mol), 9-anthracene methyl methacrylate (27.63 g, 0.10 mol), 2,2'-azobis(2-methylpropionitrile) (6.41 g, 0.03 mol), and anisole (100 g) were added to a flask, degassed by three freeze-thaw cycles, and then filled with a nitrogen atmosphere. This mixture was heated in an oil bath at 85°C for 16 hours. This mixture was diluted with tetrahydrofuran and precipitated in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated again in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated in DI water. The polymer was collected and dried in a vacuum oven. Pale yellow powder, 63.6 g (yield 94.0%); Mn 43,532 g / mol, Mw 89,934 g / mol, PDI 2.07). 1 Composition determined based on 1H NMR (82.5 / 17.5).
[0176] Preparation 1: P(MMA-r-AMMA)(1) was dissolved in ArF thinner as a 1 wt% solution. 1,1'-(methylenedi-4,1-phenylene)bismaleimide was dissolved in ArF thinner as a 1 wt% solution. 9.44 g of P(MMA-r-AMMA) as a 1 wt% solution and 0.56 g of 1,1'-(methylenedi-4,1-phenylene)bismaleimide as a 1 wt% solution were mixed and filtered through a 0.2 micron disc filter.
[0177] Preparation 2: P(MMA-r-AMMA)(1) was dissolved in ArF thinner as a 1 wt% solution. 1,1'-(methylenedi-4,1-phenylene)bismaleimide was dissolved in ArF thinner as a 1 wt% solution. 9.71 g of P(MMA-r-AMMA) as a 1 wt% solution and 0.29 g of 1,1'-(methylenedi-4,1-phenylene)bismaleimide as a 1 wt% solution were mixed and filtered through a 0.2 micron disc filter.
[0178] Polymer synthesis example 2: Synthesis of poly(methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylate (85 / 15): Methyl methacrylate (14.6 g, 0.15 mol), 3-(trimethoxysilyl)propyl methacrylate (9.1 g, 0.04 mol), 2,2'-azobis(2-methylpropionitrile) (0.36 g, 2.2 mmol), and 2-butanone (36 g) were added to a flask, degassed by three freeze-thaw cycles, and then packed under a nitrogen atmosphere. This mixture was heated in an oil bath at 85°C for 16 hours. This mixture was diluted with tetrahydrofuran and precipitated in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated again in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated in DI water. The polymer was collected and dried in a vacuum oven. White powder, 22.3 g (yield 93.8%); Mn 16,265 g / mol, Mw 28,481 g / mol, PDI 1.75. 1 Composition determined based on 1H NMR (79.2 / 20.8).
[0179] Preparation 3: P(MMA-r-TMOSiPrMA)(2) was dissolved in ArF thinner as a 1 wt% solution. 7.81 g of the 1 wt% solution of P(MMA-r-TMSiOSiPrMA) and 2.19 g of the 1 wt% solution of bis(tetrabutylammonium)pentane-1,5-bis(olate) were mixed and filtered through a 0.2 micron disc filter.
[0180] Polymer synthesis example 3: Synthesis of poly(methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylate)-co-2-trimethylsilyloxyethyl methacrylate): Methyl methacrylate (13.8 g, 0.14 mol), 3-(trimethoxysilyl)propyl methacrylate (9.79 g, 0.04 mol), 2-trimethylsilyloxyethyl methacrylate (3.99 g, 0.02 mol), 2,2'-azobis(2-methylpropionitrile) (0.41 g, 2.5 mmol), and methyl isobutyl ketone (42 g) were added to a flask, degassed by three freeze-thaw cycles, and then filled with a nitrogen atmosphere. This mixture was heated in an oil bath at 85°C for 16 hours. This mixture was diluted with tetrahydrofuran and precipitated in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated again in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated in DI water. The polymer was collected and dried in a vacuum furnace. White powder, 26.2 g (yield 94.3%); Mn 17,799 g / mol, Mw 34,024 g / mol, PDI 1.91. Based on 1H NMR (69.8 / 20.7 / 9.5).
[0181] Polymer Synthesis Example 4: Synthesis of Poly(methyl methacrylate-co-3-(trimethoxysilyl)propyl methacrylate)-co-glycidyl methacrylate Methyl methacrylate (14.4 g, 0.14 mol), 3-(trimethoxysilyl)propyl methacrylate (10.2 g, 0.04 mol), glycidyl methacrylate (2.9 g, 0.02 mol), 2,2'-azobis(2-methylpropionitrile) (0.41 g, 2.5 mmol), and methyl isobutyl ketone (42 g) were added to a flask, degassed by three freeze-thaw cycles, and then packed under a nitrogen atmosphere. This mixture was heated in an oil bath at 85°C for 16 hours. This mixture was diluted with tetrahydrofuran and precipitated in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated again in hexane. The supernatant was decanted, and the remainder was dried in a vacuum oven. The remainder was redissolved in THF and precipitated in DI water. The polymer was collected and dried in a vacuum oven. White powder, 26.8 g (yield 96.5%); Mn 19,113 g / mol, Mw 95,995 g / mol, PDI 5.02.
[0182] Scheme 1 shows a general reaction scheme for producing the polymers in polymer synthesis examples 6 and 7.
[0183] [ka] Figure 1 shows a typical 1H NMR spectrum of P(MMA-r-TMOSiPrMA-r-TMSHEMA).
[0184] Synthesis of (TBA)2-PD: bis(tetrabutylammonium)pentane-1,5-bis(olate) Bis(tetrabutylammonium)pentane-1,5-bis(olate) was prepared as a 1 wt% solution by mixing 1,5-pentanediol (0.10 g, 1.0 mmol), tetrabutylammonium hydroxide (1.54 g, 1.9 mmol), and ArF thinner (55 g).
[0185] [ka] Characteristics Table 1 shows the composition of the tested formulations. These formulations were prepared by dissolving the listed polymers and crosslinking agents in ArF thinner (PGMEA:PGME70:30) to 0.4% or 1% by weight solutions. The wt% indicated for crosslinking agents, where present, is relative to the total solid weight of the solution. After dissolution, each sample was filtered through a 0.2 micron disc filter.
[0186] [Table 1]
[0187] MPBM: 1,1'-(methylenedi-4,1-phenylene)bismaleimide (1,1'-(methylenebis(4,1-phenylene))bis(1H-pyrrole-2,5-dione) was obtained from Sigma-Aldrich.
[0188] [ka] Immersion test of the compound Table 2 shows the results of immersion tests performed on crosslinked films formed using these compositions. These immersion tests demonstrated that all of these formulations possessed satisfactory crosslinking for use as polarity-inducing MATs.
[0189] [Table 2]
[0190] Immersion test of the compound Block copolymer formulation A reference polymer synthesis example was dissolved in ArF thinner to prepare a 0.4 wt% solution, which was then filtered using 0.2 μm PTFE.
[0191] Figure 2 shows an SEM image showing the parallel shape of PME-7102 (Lo=29nm, film thickness 35nm at 1500rpm) annealed in air at 250°C for 2 minutes on a crosslinked film of the material for synthesis example 2 on a silicon wafer. The absence of a fingerprint pattern indicates that the underlying MAT layer pinned the upper block copolymer by interacting with the polar methyl methacrylate of the upper block copolymer. This application relates to the invention described in the claims, but the disclosure of this application also includes: 1. A random copolymer of structure (A), Alkyl-containing repeating units of structure (I), however, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl, and n1 is the total number of repeating units; The repeating unit containing trialkylsilyloxy of structure (II), where R II This is part of the structure (A-1), and R m2 is H or C1-C4 alkyl, L 1 R is either a direct valence bond or a C1-C8 alkylene moiety. IIa 、R IIb and R IIc n2 is independently selected from C1-C4 alkyl groups, and n2 is the total number of repeating units; At least one type of crosslinkable repeating unit of structure (III) (in this case, R III (is a part of structure (A-2) or (A-3)), or two different types of repeating units of structure (III) (in this case, R III (which is either part of structure (A-2) or part of structure (A-3), however Rs 1 is a C1-C4 alkyl group, Rs is a C1-C4 alkyl group, x is 0, 1, or 2, and L 2 and L 3 R is independently either a direct valence bond or a C1-C10 alkylene moiety, and ox n3 is the aliphatic moiety containing oxirane, and n3 is the total number of repeating units; Structure (A) shows two terminal groups, one of which is H and the other is Rr, Rr 1 and Rr 2 The methyl moiety is substituted with, however, Rr 1 、Rr 2 Rr is independently selected from C1-C8 alkyl groups, and Rr is either a cyano moiety (-CN) or a carbonyl alkyl moiety (-C(=O)-Ri), where Ri is a C1-C8 alkyl group or an aryl moiety; The random copolymer comprising the above. [ka] 2. The repeating unit essentially consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is a single type of crosslinkable repeating unit of structure (III), and R III The copolymer described in 1. above, wherein the copolymer is a part of structure (A-2) or structure (A-3). 3. The repeating unit essentially consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is two different types of repeating units of structure (III), where R III The copolymer described in 1. or 2. above, wherein the copolymer is a part of structure (A-2) or structure (A-3). 4. The repeating unit consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is a single type of crosslinkable repeating unit of structure (III), and R III The copolymer described in any one of 1. to 3. above, which is a part of structure (A-2) or structure (A-3). 5. The repeating unit consists of repeating units of structures (I), (II), and (III), wherein the repeating unit of structure (III) is two different types of repeating units of structure (III), where R III The copolymer according to 1. or 3. above, wherein is a part of structure (A-2) or structure (A-3). 6. R III A copolymer according to any one of 1. to 5. above, wherein the copolymer has structure (A-2). 7. R III The copolymer according to any one of 1. to 6. above, wherein has structure (A-2) and x is 1. 8. R III The copolymer according to any one of 1. to 6. above, wherein the structure is (A-2) and x is 2. 9. R III The copolymer according to any one of 1. to 6. above, wherein has structure (A-2) and x is 0. 10. R III has structure (A-2), where L 2 The copolymer according to any one of 1. to 9. above, wherein is a C2-C4 alkylene moiety. 11. R III A copolymer according to any one of 1. to 10., wherein the copolymer has structure (A-2a).
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
change
Claims
1. A random copolymer having structure (D), ...Alkyl-containing repeating units of structure (I), however, R I R is a C1-C8 alkyl group, m1 is H or C1-C4 alkyl, and n1 is the total number of repeating units; ...Cross-linkable repeating unit of structure (III), however, R m3 is H or C1-C4 alkyl, and R III This is part of the structure (A-2), where Rs 1 is a C1-C4 alkyl group, Rs is a C1-C4 alkyl group, x is 0, 1, or 2, and L 2 n3 is either a direct valence bond or a C1-C10 alkylene moiety, and n3 is the total number of repeating units; ・・two terminal groups shown in Structure (D), one of which is H, and the other is Rr, Rr 1 and Rr 2 is a substituted methyl moiety, provided that Rr 1 and Rr 2 are independently selected from C1 to C8 alkyl, and Rr is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), where Ri is a C1 to C8 alkyl or aryl moiety; The random copolymer comprising; - At least one crosslinking agent of structure (B), however, L 5 is a C4-C8 alkylene having a length of at least four carbon atoms, and R a1 , R a2 , R a3 and R a4 is independently selected from C4-C8 alkyl groups; and • Organic solvents for spin casting; A polar pinned MAT composition for use in induced self-assembly processes, including the above. 【Chemistry 1】
2. The polar pinning MAT composition according to claim 1, wherein the copolymer of structure (D) consists of repeating units of structures (I) and (III).
3. R m1 The polarity pinning MAT composition according to claim 1 or 2, wherein is methyl.
4. R m1 The polarity pin-fastening MAT composition according to claim 1 or 2, wherein is H.
5. The polar pin-fastened MAT composition according to claim 1 or 2, wherein in structure (A-2), x is 1.
6. The polar pin-fastened MAT composition according to claim 1 or 2, wherein in structure (A-2), x is 2.
7. The polarity pinned MAT composition according to claim 1 or 2, wherein x is 0 in structure (A-2).
8. L 2 The polar pin-fastened MAT composition according to claim 1 or 2, wherein the C2-C4 alkylene portion is the C2-C4 alkylene portion.
9. R III The polar pin-fastening MAT composition according to claim 1 or 2, wherein the structure is (A-2a). 【Chemistry 2】
10. R III The polar pin-fastening MAT composition according to claim 1 or 2, wherein the structure (A-2b) is... 【Transformation 3】
11. R m3 The polarity pinning MAT composition according to claim 1 or 2, wherein is methyl.
12. R m3 The polarity pin-fastening MAT composition according to claim 1 or 2, wherein is H.
13. The polar pinned MAT composition according to claim 1 or 2, wherein in the polymer of structure (D), the mol% of the repeating units of structure (I) is in the range of 70 mol% to 90 mol%, and the mol% of the repeating units of structure (III) is in the range of 5 mol% to 30 mol%, and furthermore, the sum of the mol%s of the repeating units of structures (I) and (III) is equal to 100 mol%.
14. In the crosslinking agent of structure (B), L 5 The polar pin-fastening MAT composition according to claim 1 or 2, wherein the C4-C6 alkylene is used.
15. The polar pin-fastening MAT composition according to claim 1 or 2, wherein the crosslinking agent of structure (B) has structure (B-1). 【Chemistry 4】
16. The polar pinning MAT composition according to claim 1 or 2, comprising 0.2% by weight to 1.98% by weight of the copolymer, 0.02% by weight to 0.04% by weight of the crosslinking agent, and 98.0% by weight to 99.78% by weight of the organic solvent for spin casting, wherein the sum of these weight percentage ranges is equal to 100% by weight.
17. A method for forming a crosslinked pinned film, the following steps: id) A step of coating a substrate with the polar pin-fastening MAT composition according to claim 1 or 2; i) A step of crosslinking the coated substrate by baking it in air at a temperature of 230 to 250°C for 30 seconds to 3 minutes; iii) Wash with a cleaning solution for 1 to 4 minutes to remove soluble material; ivd) Dry the coating to form the crosslinked pinning layer on the substrate; The method, including the method described above.
18. A method for inducing a multiplied pattern in a block copolymer film, i.e.) A step of providing a block copolymer having two or more spontaneously separating blocks; iii) Step of providing a substrate; iii) The step of forming a crosslinked pinning layer according to claim 17; and iv) The step of placing a block copolymer on at least a portion of the crosslinked pinning layer; The method, including the method described above.
19. v) A step of forming a pattern in the crosslinked pinned layer by a lithography process before arranging the block copolymer; vie) optionally, a second coating is applied to the pattern, wherein the second coating is a neutral layer; The method according to claim 18, further comprising:
20. Use of the polar pinning MAT composition according to claim 1 or 2 for forming a crosslinked pinning film on a substrate, or for inducing a multiplied pattern in a block copolymer film.
Citation Information
Patent Citations
Composition of a neutral layer for induced self-assembled block copolymers and method thereof
JP2014528015A
Substrate agent composition and manufacturing method of structure containing phase separation structure
JP2016108435A
Substrate composition for promoting self-assembly, and method of manufacture and use.
JP2017513032A
Resin composition and resist
JP2021024929A
Underlayer composition for promoting self assembly and method of making and using
US9093263B2